2014
DOI: 10.1007/s12194-014-0264-3
|View full text |Cite
|
Sign up to set email alerts
|

Method for detection of aspiration based on B-mode video ultrasonography

Abstract: In this study, we aimed to develop a new method for detection of aspiration based on B-mode video ultrasonography and to evaluate its performance. To detect aspirated boluses by B-mode video ultrasonography in patients with dysphagia, we placed a linear array transducer above the thyroid cartilage and observed the area around the vocal folds. Forty-two ultrasonographic measurements were obtained from 17 patients with dysphagia who also underwent videofluoroscopy or videoendoscopy measurements at the same time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…In our previous study, which aimed at detecting aspiration, we also found a higher disagreement between US examination and FEES for low-viscosity boluses [12]. The size of the boluses may affect the visualization of pharyngeal post-swallow residue.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…In our previous study, which aimed at detecting aspiration, we also found a higher disagreement between US examination and FEES for low-viscosity boluses [12]. The size of the boluses may affect the visualization of pharyngeal post-swallow residue.…”
Section: Resultsmentioning
confidence: 80%
“…This study used US images that were obtained in the previous study to develop a method to detect aspiration by US examination [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy, however, that the USG of swallowing, as well as all the other imaging techniques, requires the speechlanguage therapist to have specific training with a specialized professional and to have basic knowledge of the appearance of the anatomic structures of the oropharynx, imaging procedures, and operation of the system (4) . There are studies that use the ultrasound of the tongue movement to characterize the oral phase of oropharyngeal swallowing (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . Among these studies, some prioritized a qualitative description (1,(5)(6)(7) whereas others propose quantitative measures (8)(9)(10)(11)(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies that proposed the quantitative measures with the use of ultrasound (US) (8)(9)(10)(11)(12)(13)(14)(15) , it was observed that the adoption of different parameters, such as, duration of propulsion of the food bolus (sec); displacement of the lateral pharyngeal walls (cm); speed (mm/s), amplitude (mm), and duration (s) of the tongue movement during swallowing; in addition to the displacement of the hyoid bone, both in terms of duration (ms) and distance (mm).…”
Section: Introductionmentioning
confidence: 99%